2019
DOI: 10.1007/s11739-019-02025-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, open-label, cross-over clinical study to evaluate the pharmacokinetic profiles of cigarettes and e-cigarettes with nicotine salt formulations in US adult smokers

Abstract: E-cigarettes containing ‘nicotine salts’ aim to increase smoker’s satisfaction by improving blood nicotine delivery and other sensory properties. Here, we evaluated the pharmacokinetic profiles and subjective effects of nicotine from two e-cigarette device platforms with varying concentrations of nicotine lactate (nicotine salt) e-liquid relative to conventional cigarettes. A randomised, open-label, cross-over clinical study was conducted in 15 healthy US adult smokers. Five different e-cigarette products were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
74
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 30 publications
10
74
2
1
Order By: Relevance
“…The evidence supporting a role for e-cigarettes in smoking cessation/reduction has not been straightforward. One study of 15 individuals, lead by a popular manufacturer of e-cigarettes, observed that the urge to smoke was reduced by e-cigarettes at plasma levels of nicotine that were lower than obtained with conventional cigarettes [29]. Another prospective 6-month study of 40 smokers with no intention of quitting found a sustained 50% reduction in cigarettes/day at week 24 in 13/40 participants and a sustained 80% reduction in 5/40 participants.…”
Section: E-cigarette Use Patterns and Their Utility As A Smoking Cessmentioning
confidence: 99%
“…The evidence supporting a role for e-cigarettes in smoking cessation/reduction has not been straightforward. One study of 15 individuals, lead by a popular manufacturer of e-cigarettes, observed that the urge to smoke was reduced by e-cigarettes at plasma levels of nicotine that were lower than obtained with conventional cigarettes [29]. Another prospective 6-month study of 40 smokers with no intention of quitting found a sustained 50% reduction in cigarettes/day at week 24 in 13/40 participants and a sustained 80% reduction in 5/40 participants.…”
Section: E-cigarette Use Patterns and Their Utility As A Smoking Cessmentioning
confidence: 99%
“…These latter devices are comparatively simple and easy to use. Pod systems usually contain highly concentrated nicotine salt formulations and have recently been demonstrated to deliver nicotine nearly equally efficient as combustible cigarettes (Bowen and Xing 2014;O'Connell et al 2019). The high nicotine content of up to 5% (approximately 58 mg/mL), the resulting high pH value of the vapor and the high proportion of free-base nicotine would normally lead to airway irritation (Duell et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that nicotine is being absorbed more efficiently through JUUL pods than through combustible cigarettes — likely a result of cigarette nicotine being combusted into sidestream smoke and JUUL pods’ nicotinic formulation [ 13 ]. JUUL pods contain a protonated form of nicotine known as nicotine salts [ 14 ], of which the absorption resembles freebase nicotine seen in cigarettes [ 15 , 16 ] but has a smoother feel when inhaled and does not taste as bitter [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%